The Relationship between Self-Control and Cyber Aggressive Behavior in Adolescent Social Media Users - Koroh, Riska Kamelia; Benu, Juliana Marlin Yustrianti; Keraf, M. K. P. Abdy (Universitas Nusa Cendana, 2025)
Cyber ​​aggression has a serious impact on the mental and social well-being of adolescents. This study aims to fill the gap by exploring the relationship between self-control and cyber aggression in adolescent social media users in Kupang City. The sample determination was carried out using a purposive sampling technique. The data analysis techniques employed were normality tests, linearity tests, and correlation tests. he test results revealed a correlation between self-control and cyber aggression, indicating a significant negative relationship between the self-control variable and the cyber aggression variable. The results of the measurement of the level of self-control obtained 237 participants (62.5%) in the high category, so the level of self-control among adolescent social media users in Kupang City was in the high category. There were 247 participants (65.2%) in the low category, so cyber aggression in adolescent social media users in Kupang City was in the low category.